Crimes and War Crimes: William Hodge & Co. and the Public Understanding of the Holocaust in Post-World War II Britain. Issue 1 (2nd January 2019) - Stewart, Victoria
Abstract: This article considers how existing discourse about crime in Britain was adapted to accommodate and understand war crimes in the wake of World War II. Focusing on the representation of the British-run trial of Josef Kramer and others for crimes committed at Belsen and Auschwitz, which was held at Lüneberg in the autumn of 1945, I compare newspaper reporting with the volume about the trial produced by William Hodge & Co. In adapting the format of their existing "Notable Trials" series, Hodge & Co. promoted a perception of war crimes that tended to downplay their specificity, and this can help in understanding why the Holocaust was only belatedly recognized as a discrete and particular series of historical events.